Facilitating the comprehension of human-computer interaction design intent within a software team - Myhill, Carl (Cranfield University, 1998)
A large proportion of today’s software development is unsuccessful. One reason for this is thought to be lack of attention to the user. Maintaining a user-centred focus during software production is regarded as a major problem. Introducing an HCI designer role into the software team (they usually function as external advisors) is thought to be a means of addressing this problem. Issues surrounding the introduction of an HCI designer role into software teams were explored by a qualitative investigation. Participant-observation studies were carried out on two year-long software projects, with the researcher performing the role of HCI designer within the software teams. Aspects of comprehension within the team were found to be fundamental to successful collaboration. Prototypes were found to be an effective means of facilitating team members' comprehension of HCI design intent, and of maintaining conceptual integrity. However, this use of prototypes was flawed because they introduced the potential for ambiguity and they were inaccessible. Focusing on the collaboration of the HCI designer and programmers, requirements for a prototype-centred explanation tool were specified to exploit the potential of prototyping to facilitate comprehension, by addressing the flaws discovered. Such a tool, called ‘ProtoTour’, was designed and implemented, based on the requirements specified. An experiment was conducted with 22 commercial programmers to ascertain whether a ProtoTour representation of an existing, commercially developed prototype, facilitated comprehension more effectively and was more accessible than a conventional prototype. Results of the experiment found that programmers using ProtoTour gained a significantly better understanding of HCI design intent, than programmers using a conventional prototype. Those using ProtoTour also asked the HCI designer significantly fewer questions about the HCI design intent. Results suggest that prototype-centred explanation tools have the potential to improve programmers’ comprehension of HCI design intent. Introducing an HCI designer into a software team was found to be an effective way of improving the user-centred focus of software during production. A prototype-centred explanation tool appears to have potential as a means of helping programmers comprehend HCI design intent.
Keywords: Waterfall lifecycle